Implementasi Nilai-Nilai Moderasi Beragama dalam Al-Qur'an dan Pengukuhan Desa Sadar Kerukunan di Kota Banda Aceh - Faisal, Muhammad (CENDEKIA: Jurnal Studi Keislaman, 2023)
The life of the Indonesian people, which consists of ethnic, cultural and religious differences, tends to experience several dynamics. These dynamics often lead to disputes and disputes, so that serious attention is needed from the government. So far, several efforts have been made, including forming or strengthening harmony-conscious villages, as has been done by the Banda Aceh City Government. The harmony-aware village was given to two villages, namely Kampung Mulia Village and Peunanyoeng Village, of course based on the indicators that were used as conditions for awarding the award. On the other hand, the Central Government through the Ministry of Religion of the Republic of Indonesia sparked a concept to create harmony in people's lives namely "religious moderation". However, the question is, what is the relationship between the harmony-conscious village and the concept of religious moderation, this is the formulation of the problem to be answered in this research. This type of research is field research with in-depth interview methods, and uses a descriptive-analytic approach. In this study, the answer was found that a village that is aware of harmony is an effort by the government to care for and maintain a harmonious life among religious people and that in a village that is aware of harmony, there are values ​​of religious moderation, namely: Perpendicular (I'tidal), Middle (tawassuth) , tolerance (tasamuh), deliberation (shura), reform (ishlah), pioneering (qudwah), anti-violence (al-la'unf) in the cultural realm (I'yar al-'urf), and citizenship/love for the motherland (muwathanah ). These values ​​flourish so as to create a harmonious life.